In Vitro Degradation Behaviors of Manganese-Calcium Phosphate Coatings on an Mg-Ca-Zn Alloy. (13th February 2018) - Su, Yichang; Su, Yingchao; Zai, Wei; Li, Guangyu; Wen, Cuie
Abstract : In order to decrease the degradation rate of magnesium (Mg) alloys for the potential orthopedic applications, manganese-calcium phosphate coatings were prepared on an Mg-Ca-Zn alloy in calcium phosphating solutions with different addition of Mn 2+ . Influence of Mn content on degradation behaviors of phosphate coatings in the simulated body fluid was investigated to obtain the optimum coating. With the increasing Mn addition, the corrosion resistance of the manganese-calcium phosphate coatings was gradually improved. The optimum coating prepared in solution containing 0.05 mol/L Mn 2+ had a uniform and compact microstructure and was composed of MnHPO4 ·3H2 O, CaHPO4 ·2H2 O, and Ca3 (PO4 )2 . The electrochemical corrosion test in simulated body fluid revealed that polarization resistance of the optimum coating is 36273 Ωcm 2, which is about 11 times higher than that of phosphate coating without Mn addition. The optimum coating also showed the most stable surface structure and lowest hydrogen release in the immersion test in simulated body fluid.